THE EFFECT OF TOLERANCES ON SWITCHING TRACTION MOTORS TRANSIENT - Dubynets, L. V.; Shapovalov, A. V. (Science and Transport Progress, 2008)
Dependence of the traction engine sparking degree on practical realization of tolerances on geometric parameters of the magnetic circuit of additional poles under transition modes during the trolley take-off from contact mains and further recovering the feeding is shown in the article.